2021
DOI: 10.1111/add.15709
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐national validation of the social media disorder scale: findings from adolescents from 44 countries

Abstract: Background and aims There is currently no cross‐national validation of a scale that measures problematic social media use (SMU). The present study investigated and compared the psychometric properties of the social media disorder (SMD) scale among young adolescents from different countries. Design Validation study. Setting and participants Data came from 222 532 adolescents from 44 countries participating in the health behaviour in school‐aged children (HBSC) survey (2017/2018). The HBSC survey was conducted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 57 publications
2
43
3
2
Order By: Relevance
“…Five or more positive answers out of nine points to the presence of PUsocial [26]. A recent cross-national analysis of adolescents' psychometric characteristics in 44 countries showed a high level of validity and reliability for the SMDS [27].…”
Section: Internet Addiction Measurementmentioning
confidence: 97%
“…Five or more positive answers out of nine points to the presence of PUsocial [26]. A recent cross-national analysis of adolescents' psychometric characteristics in 44 countries showed a high level of validity and reliability for the SMDS [27].…”
Section: Internet Addiction Measurementmentioning
confidence: 97%
“…Six or more positive answers suggested that the respondent is a problematic user (recorded as 1); others were recorded as 0. This measure has been validated across 44 countries, including Israel, and found to be adequate (Boer et al, 2022).…”
Section: Measurements Problematic Social Media Usementioning
confidence: 99%
“…All items are rated on a five-point Likert scale ranging from 1 = never/almost never to 5 = almost all the time throughout the day. In line with previous studies, the respondents' answers were recoded (Boer et al, 2020(Boer et al, , 2022: those who answered "almost all the time throughout the day" on at least one item were classified as 1 = intense user, and the rest were classified as 0 = non-intense users. The measure has been used previously in Israel after a validation process (e.g., Boniel-Nissim et al, 2022).…”
Section: Intensive Social Media Usementioning
confidence: 99%
“…Hence, the SMD scale appears to be more comprehensive than the existing scales. The 9-item SMD scale has been validated in adolescent groups in China ( 19 ), Turkish ( 20 ), and Netherlands ( 21 ), as well as across 44 countries ( 22 ), suggesting the validity of the SMD-9 scale in measuring problematic usage of social media in adolescents. Furthermore, the 27-item SMD scale, consist of three items for each of the nine DSM-5 criteria, has been found to be more specific and comprehensive in describing social media addiction behavior as compared to SMD-9 scale.…”
Section: Introductionmentioning
confidence: 99%